Description of the antipredatory head-wobble behaviour in Chilean rear-fanged snakes Tachymenis peruviana Wiegmann, 1835 and Tachymenis chilensis coronellina Werner, 1898 (Serpentes, Dipsadidae) - Reyes Olivares, Claudio.; Vera Quispe, Alex.; Zúñiga, Alejandro; Urra, Félix A. (Pensoft Publishers, 2022)
In this work, we describe the first records of head-wobble behaviour for Tachymenis peruviana and T. chilensis coronellina. We analyse this behaviour (occurrence, frequency) and accompanying displays in both species. Of particular note is that T. ch. coronellina exhibited more frequent head-wobbling than T. peruviana and, in both records, wind activity was observed during this antipredatory behaviour.
Keywords: Antipredatory behaviour; Behavioural camouflage; Colubrid snakes